Laurentian provenance and an intracratonic tectonic setting for the Moine Supergroup, Scotland, constrained by detrital zircons from the Loch Eil and Glen Urquhart successions - Cawood, Peter Anthony; Nemchin, A A; Strachan, R A; Kinny, P D; Loewy, S (2004)
Detrital zircons in psammite from the type section of the Loch Eil Group of the Maine Supergroup, NW Scotland, and from an unnamed quartzose psammite, interstratified with marble, at Glen Urquhart yield similar U-Pb detrital zircon ages ranging from c. 2300 to 900 Ma. Both samples show age peaks at c. 1680-1630 Ma, 1510-1490 Ma, 1430-1330 Ma and 1110-1040 Ma. Archaean age grains are absent and Palaeoproterozoic grains older than 1800 Ma are rare. Sediment accumulation occurred in the early Neoproterozoic post c. 900 Ma but prior to emplacement of the 870 Ma West Highland granite gneiss. The Glen Urquhart sample has previously been considered to form part of the Albynian sequence lying between the Moine and Dalradian supergroups. The similar detrital zircon age signature of the two samples is consistent with the Glen Urquhart material representing part of the upper Moine succession. In both samples, detrital age peaks at around 1650 Ma and 1500 Ma correspond closely to the Labradorian and Pinware magmatic events in NE Laurentia and Baltica whereas the younger age peaks at c. 1400 and 1100 Ma correspond to phases of the Grenville orogen in Laurentia. The presence of detritus at c. 1650 Ma argues against input from Amazonia, which lacks any recorded magmatic activity in the range 1700-1600 Ma. The absence of Archaean and late Palaeoproterozoic detritus, which is present in Laurentia-derived units younger than the Maine, such as the Dalradian and Western Newfoundland strata, suggests that the Labradorian and Pinware magmatic arcs retained sufficient topographic relief to mask and block any input of older detritus into the Neoproterozoic Moine basin. The Laurentian provenance of the zircons argues against an exotic origin for the Moine Supergroup. Palaeogeographical reconstructions suggest that the Moine succession accumulated in an intracratonic setting within Rodinia near the nexus of Laurentia, Baltica and Amazonia. Closure during the mid-Neoproterozoic of this site of lithospheric extension along with its record ...